Beyond the sky and the earth : a journey into Bhutan - Zeppa, Jamie (New Delhi : Timeless Books, 2013)
Jamie Zeppa made a life-altering decision at the age of 24 when she left an academic career to join a two-year teaching programme for young Canadians in Bhutan. This book recounts the difficulties she encountered living within an alien culture, but also writes with awe of the beauty of the country.
Keywords: Zeppa, Jamie -- Homes and haunts -- Bhutan; Description and travel. -- Bhutan; Social life and customs. -- Bhutan